PRAKTIK TAJDIDUN NIKAH PADA MASYARAKAT PERSPEKTIF HUKUM ISLAM (Studi Kasus di Desa Sidokumpul Kecamatan Bungah Kabupaten Gresik) - Khosiatul Qomariyah; Abdullah Afif (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Marriage is the process of uniting a man and a woman through ijab qabul. Behind this process, there is divine wisdom, where strengthening the bonds of marriage, maintaining household harmony is a form of caution towards the validity of marriage. This tradition is known by local terms such as